BAD EFFECT OF PATRIARCHAL CULTURE IN NAWAL EL SADDAWI’S NOVEL WOMAN AT POINT ZERO - Adinda Liasna Munthe; Sri Wulan (Universitas Islam Sumatera Utara, 2023)
This study raises the theme of patriarchal culture experienced by the characters in Nawal El Saddawi's novel Woman at Point Zero. The novel is considered a feminist novel because it reveals many dimensions of oppression against women and the characters' struggle against gender discrimination to get their rights. Firdaus is the main character, who lives her life in a very tight patriarchal culture from pre-marriage, marriage, and post-marriage. The research in the novel is motivated by the social reality of patriarchal ideology ingrained in society so that women are always in the realm of domesticity. The purpose of this research is to explain the bad effects of patriarchal culture to the protagonist. The data obtained from the novel are analyzed using a qualitative descriptive method because it is used to describe and interpret the subject matter. The findings of this study indicate that there are three bad effects of patriarchal culture in the novel: violence against women, subordination, and sexual exploitation.